Developing Microphysiological Systems of Bone Development, Physiology, and Repair - Whelan, Ian (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2021)
Accurate models of human tissues and organ systems are foundational in our efforts to better understand human physiology. In the context of bone, a number of in vitro and in vivo models have been developed that facilitate study of bone at the cell, tissue and whole organism level. However, despite years of research, our knowledge of fundamental bone physiology is still limited to the extent that the cause of prominent bone diseases is still unknown. Microphysiological systems (MPSs), or organ-on-chip systems, represent a promising new platform technology with potential to augment current model systems and facilitate advanced bone research by recreating key bone functions in vitro. To realise this potential, the overall objective of this thesis is to develop MPSs of bone development, physiology and repair. The first aim of this thesis was to establish methods of vascularising tissues within microfluidic devices as templates for generating physiologically relevant bone MPSs. Specifically, methods facilitating endothelial cell vasculogenesis in MPS devices with hBMSCs acting as a support cell were developed. It was observed that hBMSCs could directly support HUVEC vasculogenesis when cultured in the same hydrogel, or indirectly by the release of paracrine factors when cultured in separate hydrogels within an MPS device. This provides a framework to engineer bone with physiologically relevant vasculature in vitro. The second aim of this thesis was to develop a model of endochondral ossification (EO) to mimic bone development/repair within a MPS device. hBMSC spheroids mimicking the different stages of cartilage maturity in developing/regenerating bone were vascularised to model key events during the transition of cartilage to bone in EO. The model showed evidence of key EO events such as the angiogenic switch that occurs between mature and hypertrophic cartilage, and vascular induced pluripotency. Vascular development was found to depend on the maturity of the cartilage spheroids, while in turn the phenotype of the developing cartilage was altered by the invading vasculature. The final aim of the thesis was to develop a model of bone tissue capable of recreating the function of osteoblasts and osteocytes in mature bone, as these cells specifically are critical to bone remodelling and endocrine function. A collagen nanohydroxyapatite hydrogel was developed that can drive osteogenesis of hBMSCs, manifesting in the secretion of factors clinically relevant to bone remodelling and endocrine function. Thus, this engineered bone tissue can recreate mature bone function using an accessible human derived cell source for use in MPSs. In summary, the work presented in this thesis establishes advanced models of human bone development/regeneration and mature bone function in MPS devices. Such in vitro systems have potential to improve our understanding of basic bone physiology, and hence accelerate research that will improve outcomes for those suffering with bone related conditions.
APPROVED
Keywords: Organ on Chip; Bone; Cartilage; Microphysiological System